VARIETALS RESISTANCE AND SUSCEPTIBILITY IN MUSTARD (BRASSICA CAMPESTRIS L.) GENOTYPES AGAINST APHID MYZUS PERSICAE (SULZER) (HOMOPTERA: APHIDIDAE) - Sarwar, M.; Ahmad, N.; Khan, G. Z.; Tofique, M. (The Nucleus, 2020)
The exploitation of resistant cultivars is an imperative, simple, practical and flexible way to cope with insect pests incidence. Thirty genotypes of mustard (Brassica campestris L.) were tested for their resistance and susceptibility to aphid Myzus persicae (Sulzer) exposed under natural field conditions. Data on pest tolerance of genotypes were judged by quantitative traits such as number of aphids on each infested plant and mean dry weight of seeds per genotype. Studies observed the discrepancy in overall rates of pest invasion and seed yield contained by trailed mustard genotypes. Agati sarson (P), S-9-S-97-100/45 and S-9-S-97-100/45 were the least damaged genotypes showing their moderate resistance. Amongst other genotypes, MM-I/01-5, MM-I285 and MM-I/01-6 were the most damaged showing oversensitive response. Although the majority of genotypes were found vulnerable to pest, Agati sarson (P) and S-9-S97-100/45 due to their lowest hypersensitive response toward aphid contamination and increased pods yield could be used for the development of essential resistance in mustard plant. A marked mode of damage inflicted by aphid on the crop was noticed and the abiotic factors contributing variations in aphid infestation levels during both growing seasons were determined. Knowledge about the host plant resistance investigated can facilitate growers to choose the most appropriate cultivars as pest control strategy.